Principles of relationship differentiation - Neyer, Franz J.; Wrzus, Cornelia; Wagner, Jenny; Lang, Frieder (European Psychologist, 2011)
The authors propose a model of relationship differentiation that is based on two psychological mechanisms, the regulation of emotional closeness and the monitoring of reciprocity. Both combined are expected to define relationship systems of differential reproductive significance: Relative to others, kin relationships are predicted by higher closeness and lower reciprocity, cooperative (non-kin) relationships by lower closeness and higher reciprocity, and partner relationships by both higher closeness and higher reciprocity. These assumptions could be confirmed by two studies involving 455 young adults and 171 middle-aged couples from different family forms (i.e., traditional and patchwork families, involuntary and motivated childless couples). Effects varied primarily due to parental investment such that parental partners become less distinguishable from kin, or, in other words, more like "elected kin". Results highlight the flexibility of relationship differentiation. © 2011 Hogrefe Publishing.